2020
DOI: 10.1021/acs.accounts.0c00150
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Mediated Assembly for Particle Engineering

Abstract: Polyphenols are naturally occurring compounds that are ubiquitous in plants and display a spectrum of physical, chemical, and biological properties. For example, they are antioxidants, have therapeutic properties, absorb UV radiation, and complex with metal ions. Additionally, polyphenols display high adherence, which has been exploited for assembling nanostructured materials. We previously reviewed the assembly of different phenolic materials and their applications (Angew. Chem. Int. Ed. 2019, 58, 1904-1927),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
227
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 301 publications
(231 citation statements)
references
References 69 publications
2
227
1
1
Order By: Relevance
“…Compared to other polyphenol-based supramolecular systems, such as chelation-based nanoparticles (NPs) 24 , the pBDT-TA supramolecular networks allow tailoring of particle size, and they are stable in harsh aqueous environments (chelation-based materials typically disassemble in acid conditions 25 ). Thus, the pBDT-TA particles are envisioned to provide additional versatility and functionality for engineering NPs, while also affording a number of opportunities for subsequent modification.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other polyphenol-based supramolecular systems, such as chelation-based nanoparticles (NPs) 24 , the pBDT-TA supramolecular networks allow tailoring of particle size, and they are stable in harsh aqueous environments (chelation-based materials typically disassemble in acid conditions 25 ). Thus, the pBDT-TA particles are envisioned to provide additional versatility and functionality for engineering NPs, while also affording a number of opportunities for subsequent modification.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the antibacterial, antiinflammatory, antioxidant, and anticancer properties as well as the universal adhesion capability of natural tea polyphenols, polyphenols are fast becoming a popular class of molecules that are attracting more researchers to build various materials for bioimaging, therapeutic delivery, and other biomedical applications. [236][237][238][239][240][241][242][243][244][245][246][247][248][249][250][251] Moreover, inspired by the coordination interactions between various metal ions and polyphenols, researchers have also provided a number of functional MPNs to engineer multifunctional nanosystems. [252][253][254][255][256][257][258][259] Here, we have reviewed the structures and classification of natural polyphenols, the synthesis and properties of the polyphenol-containing nanomaterials, and various biomedical applications of polyphenol-based nanosystems.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the interactions between individual components in the mixture could create a new entity displaying modified physicochemical properties resulting in novel biological activities. Indeed, the variety of possible interactions between polyphenols (hydrogen, π , hydrophobic, chelating, covalent and electrostatic), discovered during investigations on their application as stabilisers of self-assembled nanoparticles, were shown to produce a range of structures differing in functionality 52 . It was also observed that these phytochemicals usually exert more than one type of stabilising attractive forces.…”
Section: Discussionmentioning
confidence: 99%